Role of genes GSTM1, GSTT1, and MnSOD in the development of late-onset Alzheimer disease and their relationship with APOE*4 - E. de Mendonça; E. Salazar Alcalá; M. Fernández-Mestre (Neurología (English Edition), 2016)
Introduction: Several studies have reported increased oxidation of lipids, proteins and DNA in the brains of patients with Alzheimer disease (AD). Moreover, these patients display differences in the activity and polymorphisms of the genes encoding the enzymes GST (T1, M1) and MnSOD. For these reasons, we designed a study of the variability in GSTT1, GSTM1, and MnSOD genes in healthy and AD groups from a Venezuelan population. Methods: We included 179 unrelated Venezuelan subjects classified as either AD patients (n = 79) or healthy individuals (n = 100). Presence or absence of the GSTT1/GSTM1 genes was determined using PCR-SSP, and polymorphisms of MnSOD and APOE genes were identified with PCR-RFLP. Results: The genotype GSTT1+/GSTM1− seems to favour development of AD (OR = 2.06, P = .01). The risk level is higher when it is combined with the ɛ4 allele of the APOE gene: GSTT1+/GSTM1−/ɛ3ɛ4 (OR = 3.07, P = .05), GSTT1+/GSTM1−/ɛ4ɛ4 (OR = 5.52, P = .02). The Ala-9Val polymorphism does not appear to be related to AD. However, the presence of the Ala/Ala genotype increases the risk provided by the ɛ4 allele of the APOE gene: AlaAla/ɛ3ɛ4 (OR = 3.47, P = .03), AlaAla/ɛ4ɛ4 (OR = 6.3, P = .01). Conclusions: The results support the hypothesis that impaired mitochondrial function and increased oxidative damage are involved in the pathogenesis of AD. It is important to study other genes related to oxidative stress and antioxidant pathways which could be involved in susceptibility to AD. Resumen: Introducción: Diversos estudios han descrito que en los cerebros de pacientes con enfermedad de Alzheimer (EA) hay una mayor oxidación de lípidos, proteínas y ADN. Además, en estos pacientes se ha observado diferencias en la actividad y polimorfismos de los genes que codifican las enzimas GST (T1 y M1) y MnSOD. En virtud de ello se planteó estudiar la variabilidad de los genes GSTT1, GSTM1 y MnSOD en individuos venezolanos sanos y con EA. Métodos: Se incluyeron 179 individuos venezolanos, no relacionados, agrupados en pacientes con EA (n = 79) e individuos sanos (n = 100). La presencia o ausencia de los genes GSTT1/GSTM1 se determinó por PCR-SSP y los polimorfismo de los genes MnSOD y APOE por PCR-RFLP. Resultados: El genotipo GSTT1+/GSTM1− parece favorecer el desarrollo de la EA (OR = 2,06; p = 0,01), siendo el riesgo mayor al estar en combinación con el alelo ɛ4 del gen APOE: GSTT1+/GSTM1−/ɛ3ɛ4 (OR = 3,07; p = 0,05), GSTT1+/GSTM1−/ɛ4ɛ4 (OR = 5,52; p = 0,02). El polimorfismo Ala-9Val por sí solo no parece estar relacionado con la EA, sin embargo, la presencia del genotipo Ala/Ala incrementa el riesgo que proporciona el alelo ɛ4 del gen APOE: AlaAla/ɛ3ɛ4 (OR = 3,47; p = 0,03), AlaAla/ɛ4ɛ4 (OR = 6,3; p = 0,01). Conclusiones: Los resultados apoyan la hipótesis de que el deterioro de la función mitocondrial y el aumento de daño oxidativo están involucrados en la patogénesis de la EA. Es importante estudiar otros genes relacionados con estrés oxidativo y vías antioxidantes, los cuales pudiesen estar involucrados en la susceptibilidad a desarrollar la EA. Keywords: Polymorphism, Alzheimer disease, GSTM1, GSTT1, MnSOD, Oxidative damage, Palabras clave: Polimorfismo, Alzheimer, GSTM1, GSTT1, MnSOD, Daño oxidativo